Pre‐rain green‐up is ubiquitous across southern tropical Africa: implications for temporal niche separation and model representation. Issue 2 (29th November 2016) - Ryan, Casey M.; Williams, Mathew; Grace, John; Woollen, Emily; Lehmann, Caroline E. R.
Summary: Tree phenology mediates land–atmosphere mass and energy exchange and is a determinant of ecosystem structure and function. In the dry tropics, including African savannas, many trees grow new leaves during the dry season – weeks or months before the rains typically start. This syndrome of pre‐rain green‐up has long been recognized at small scales, but the high spatial and interspecific variability in leaf phenology has precluded regional generalizations. We used remote sensing data to show that this precocious phenology is ubiquitous across the woodlands and savannas of southern tropical Africa. In 70% of the study area, green‐up preceded rain onset by > 20 d (42% > 40 d). All the main vegetation formations exhibited pre‐rain green‐up, by as much as 53 ± 18 d (in the wet miombo). Green‐up showed low interannual variability (SD between years = 11 d), and high spatial variability (> 100 d). These results are consistent with a high degree of local phenological adaptation, and an insolation trigger of green‐up. Tree–tree competition and niche separation may explain the ubiquity of this precocious phenology. The ubiquity of pre‐rain green‐up described here challenges existing model representations and suggests resistance (but not necessarily resilience) to the delay in rain onset predicted under climate change. Abstract : See also the Commentary on this article by Stock, 213: 475–477 .